A Rare Case of Mediterranean Spotted Fever and Encephalitis - Raquel Sousa Almeida; Petra M. Pego; Maria João Pinto; João Matos Costa (Case Reports in Infectious Diseases)
Mediterranean spotted fever is a tick-borne zoonotic disease caused by Rickettsia conorii. It is transmitted by the dog tick Rhipicephalus sanguineus. It usually presents as a benign self-limited disease characterized by a skin rash, high fever, and, sometimes, a characteristic ulcer at the tick bite site called tache noir. The course of this disease is usually benign, although severe manifestations have been previously described, mainly in adults. Neurological manifestations are very unusual. We present a case of Mediterranean spotted fever with encephalitis to highlight the importance of clinical suspicion, mainly in endemic areas, the potential severity of this disease, and the need of early initiation of therapy in order to prevent severe complications.